2000
DOI: 10.1007/s004380000315
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of the gene for glutamine synthetase II and two upstream genes in Streptomyces coelicolor A3(2)

Abstract: The glutamine synthetase II (GSII, encoded by glnII) activity detectable in crude extracts from Streptomyces coelicolor is low compared to the activity of glutamine synthetase I (GSI, encoded by glnA) and to that of GSII from S. viridochromogenes. We have identified and sequenced a 3.9-kb BglII-BamHI fragment carrying the glutamine synthetase II gene (glnII) from S. coelicolor. Besides glnII, this region contains four ORFs (orf1-orf4). While homologues of orf1 and orf2 were also found in the glnII region of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The main promoter should correspond to the major vegetative σ factor and its transcription start site is the adenine −79. The minor promoter shows putative elements of σ 31 (14). This sigma factor, which is more active at stationary phase, recognizes promoters of actIII (an actinorhodin structural gene) and of hrdD (a homologue of Escherichia coli rpoD ), and also the glnR P2 promoter (31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main promoter should correspond to the major vegetative σ factor and its transcription start site is the adenine −79. The minor promoter shows putative elements of σ 31 (14). This sigma factor, which is more active at stationary phase, recognizes promoters of actIII (an actinorhodin structural gene) and of hrdD (a homologue of Escherichia coli rpoD ), and also the glnR P2 promoter (31).…”
Section: Resultsmentioning
confidence: 99%
“…The overall nitrogen metabolism is regulated in S. coelicolor by complex mechanisms that involve an apparent doubling of some structural and regulatory genes (12). There are two glutamine synthetase (GS) genes in S. coelicolor : glnA (13), that encodes the GS type I (GS-I), orthologous to that found in prokaryotes, and glnII (14), which encodes GS type II (GS-II), similar to eukaryotic GS. The glnII gene appears to be present in all Streptomyces species (15), but it is absent in the related actinomycetes Mycobacterium and Corynebacterium (12).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, some proteins annotated as glutamine synthetase-like enzymes (GS-like) may represent still not recognized γ-glutamylpolyamine synthetases. Indeed, Streptomyces coelicolor A3(2) harbors two genes, glnA ( SCO2198 ) and glnII ( SCO2210 ), encoding GSI and GSII, whose function and regulation was extensively studied (Hillemann et al, 1993; Fink et al, 1999; Weisschuh et al, 2000) as well as three other genes, glnA2 ( SCO2241 ), glnA3 ( SCO6962 ), and glnA4 ( SCO1613 ), annotated as encoding putative GS-like enzymes (Rexer et al, 2006). In silico analysis of all glnA -like genes: glnA2 , glnA3 , and glnA4 across the actinobacterial genomes revealed that glnA has evolved to specialized glnA -like genes encoding proteins that might be involved in the colonization and survival in many diverse habitats (Hayward et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The glnA gene is transcribed at a constant level throughout development and GSI activity can be detected in all growth phases . The glnII gene encodes the GSII which shows high sequence similarity to eukaryotic-type GS enzymes Weisschuh et al, 2000] . GSII enzymes are characterized as heat-labile homooctamers and are typical for eukaryotes.…”
Section: Ammonium Assimilationmentioning
confidence: 99%